Operating an Advertising Programmatic Buying Platform: A Case Study - Mochón, Francisco; Gonzalvez-Cabañas, J.C. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This paper analyses how new technological developments and the possibilities generated by the internet are shaping the online advertising market. More specifically it focuses on a programmatic advertising case study. The origin of the problem is how publishers resort to automated buying and selling when trying to shift unsold inventory. To carry out our case study, we will use a programmatic online advertising sales platform, which identifies the optimal way of promoting a given product. The platform executes, evaluates, manages and optimizes display advertising campaigns, all in real-time. The empirical analysis carried out in the case study reveals that the platform and its exclusion algorithms are suitable mechanisms for analysing the performance and efficiency of the various segments that might be used to promote products. Thanks to Big Data tools and artificial intelligence the platform performs automatically, providing information in a user-friendly and simple manner.
Keywords: e-commerce; big data; online; real-time bidding; IJIMAI